Multilingual pre-school education: teachers' training and perceived needs. Results of an investigation in the municipality of Brescia and proposals for intervention - Paola Celentin (University of Bologna, 2021)
The multilingualism of the Italian school is a fact, both because of the migratory flows of the last 30 years and for historical reasons. Multilingual language education, also following the studies in the field, is therefore a necessity. The article aims to clarify the theoretical framework of transversal language education, the development of critical multilingual language awareness and it introduces the notions of school discomfort and perceived (formative) need. A case study will then be presented linked to a two-year training provided on the Brescia area, whose population will also be illustrated in terms of students with a migratory background. After presenting the research methods and the survey tools, we will analyze the degree of awareness of the multilingual question of teachers and of responsibility towards the phenomenon, trying to identify the possible causes at the origin of this perceptual position. To conclude, possible training courses will be hypothesized to increase awareness and transform school discomfort into a stimulating challenge for teacher professionalism, with the support of expert figures.